PENGARUH KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA KOPERASI KUTA MIMBA - I Komang Janur Artha Yasa; Made Yudi Darmita (Journal Research of Management, 2021)
This research aims to find out the influence of communication on employee performance at Kuta Mimba Cooperative. To find out the effect of the work environment on employee performance at Kuta Mimba Cooperative. To find out how big the influence of communication and work environment on employee performance at Kuta Mimba Cooperative. The sample used was 92 people, this study used a questionnaire in data collection. The data analysis technique used is descriptive analysis, validity and reliability testing, classical assumption test, multiple linear regression analysis, t-test analysis and coefficient of determination. The results of the analysis resulted in a regression equation model Y = 4.554 + 0.022X1 + 0.057X2. This study resulted in three conclusions, namely tthere is a partially positive and significant influence of communication on employee performance. There is a partially positive and significant influence of work environment on employee performance. The influence of communication and work environment on employee performance at Kuta Mimba Coorperative is 42,8%.